Gene expression patterns of helicoverpa armigera gut proteases - Chougule, Nanasaheb P.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Insect Biochemistry and Molecular Biology, 2005)
Relative quantification of reported gut proteinase cDNAs from Helicoverpa armigera larvae fed on various host plants (cotton, chickpea, pigeonpea, tomato and okra), non-host plant Pis (winged bean, bitter gourd, ground nut, and capsicum) and during larval development has been carried out using semi-quantitative RT-PCR. Five trypsin-like and three chymotrypsin-like proteinases were categorized as insensitive or sensitive to most of the proteinase inhibitors (Pis) and insensitive/sensitive to specific Pis based on their expression analysis. These results were supported by amino acid sequence analysis, where diverged amino acids were observed in the regions, which are reported to be involved in typical trypsin trypsin inhibitor interactions and critical for proteinase inhibitor resistance. Among exopeptidases (five aminopeptidase and three carboxypeptidase), HaAmi4 and HaAmi5 of aminopeptidase and HaCar1 of carboxypeptidase exhibited considerable differential expression. Elastase and cathepsin B-like proteinases were expressed at negligible levels. The proteases identified in the study would be ideal candidates for further interactions studies with protease inhibitors to understand the structural reasons of protease inhibitor insensitivity (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: expression; gut proteinases; Helicoverpa armigera; Proteinase inhibitors; RT-PCR